Fates of the Participants of the 1941 June Uprising in Pušalotas Rural Area of Panevėžys County - Jaskelevičius, Tadas (Genocidas ir rezistencija, 2016)
The arrival of the German army to the rural area of Pušalotas marked the end of the June 1941 Uprising. This however, was not the end of anti-Soviet activities of the partisans. They continued to arrest the retreating Soviet soldiers and Soviet activists or other suspects who lived in Pušalotas rural area. While the activities of the former participants of the Uprising were similar to those during the Uprising, they were only possible because they met the needs of the new occupation authorities. The most intensive period of activities of former insurgents was during the first few months of the Nazi occupation. At that time the majority of insurgents operated within the auxiliary squad and police units of the German occupation authorities. In this period, some of them also took part in the killings of the civilian population organised by the occupation authorities. The lack of archival data and the fact that not all information in the documents could be considered reliable prevent from identifying the exact number of such people and their motivation. Eventually the insurgents started to realise that the Nazis did not bring independence to Lithuania. At the end of 1941, anti-German moods became stronger, but did not develop into a more serious resistance movement.The arrival of the Soviet Army to Lithuania in 1944 became another critical moment in the lives of the insurgents. Some of them left Lithuania together with the retreating Germans and later, in the post-war years, settled in West Germany, United States of America, Canada and Australia. Others decided to stay in their home country. Some of the former insurgents joined the partisans in the forests, others were recruited to the Red Army. Arrests of the former participants of the 1941 June Uprising was one of the priorities of the Soviet authorities which occupied Lithuania for the second time. Between 1944 and 1950, the majority of insurgents from Pušalotas rural area were detained. All of them faced criminal charges, but sentences for the same charges varied. Collective liability, where other family members were also sentenced for the person’s crimes, an exclusive phenomenon of the Soviet legal system, was applied. Only in 1990, when Lithuania restored its independence, was it possible to exonerate the participants of the 1941 June Uprising in Pušalotas (except for the persons sentenced for the participation in the massacre of civilians), but only a few lived to see this day.
Keywords: Lithuania; Soviet occupation; antisoviet resistance; uprising; resistance